2020
DOI: 10.2196/23098
|View full text |Cite
|
Sign up to set email alerts
|

Online Public Attention During the Early Days of the COVID-19 Pandemic: Infoveillance Study Based on Baidu Index

Abstract: Background The COVID-19 pandemic has become a global public health event, attracting worldwide attention. As a tool to monitor public awareness, internet search engines have been widely used in public health emergencies. Objective This study aims to use online search data (Baidu Index) to monitor the public’s attention and verify internet search engines’ function in public attention monitoring of public health emergencies. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…depicts the characteristics of the COVID-19 outbreak in China between January 20, 2020 and March 20, 2020, through new confirmed cases, new death cases, new cured discharge cases, cumulative confirmed cases, cumulative death cases, and cumulative cured discharge cases(36).…”
mentioning
confidence: 99%
“…depicts the characteristics of the COVID-19 outbreak in China between January 20, 2020 and March 20, 2020, through new confirmed cases, new death cases, new cured discharge cases, cumulative confirmed cases, cumulative death cases, and cumulative cured discharge cases(36).…”
mentioning
confidence: 99%
“…On January 20, the con rmation of human-to-human transmission of COVID-19 was announced through television, radio, and newspaper. After being informed of their susceptibility to COVID-19, the public across China rushed to seek related information online 23,24 We found social inequalities in information-seeking behavior intensity within China. Studies have con rmed that deprived populations show relatively lower awareness of infectious diseases, including H1N1 and COVID-19 32,33 .…”
Section: Discussionmentioning
confidence: 89%
“…It is important to note that even if the local government chooses not to announce information about the pandemic in the initial stage, the potential risk may still attract public's attention due to the increase of the suspected cases and the information disclosed by the whistleblower and public opinion on the internet (Banerjee & Meena, 2021). Public's attention is an important factor in improving the efficiency of making informed decisions and responding quickly (Gong et al, 2020;Zhu et al, 2020). In order to maintain the stability of social order, public's attention may put the local government in the position of having to announce the risk information.…”
Section: Participants and Strategic Decisionsmentioning
confidence: 99%
“…While existing research has found relations between government's strategic decision, the early warnings, public's attention (Banerjee & Meena, 2021;Cao et al, 2020;Gong et al, 2020;Hyland-Wood et al, 2021;Kavanagh, 2020;Tsao et al, 2021;, research on combing with all the parties in pandemic early warning game has been found wanting. Although the government is the main party in this game system in the context of China, the current public health emergency preparedness should be improved through exploring the factors of strategic decisions of three parties and interactive mechanism of the game system.…”
Section: Introductionmentioning
confidence: 99%